Mapping Potential Land Movement of Pura Sakenan Bali - Syarifatul Ulfah; Adi Susilo (Jurnal Penelitian Pendidikan IPA, 2024)
Sakenan Temple is one of the most sacred and historic temples in Bali. Located on Serangan Island. In addition, Sakenan Temple is an area located in the tectonic pile zone that causes earthquakes. The purpose of this study was to examine possible land movement near Sakenan Temple in Bali in attempts to lessen local calamities. The sentinel 1-A picture data from August 2022–2024 is used in this research methodology. processed on SNAP software with the DinSAR approach to extract variables related to land movement. According to the findings, there was land movement in August 2022–2023 from -0.109 to 0.145 cm/year and in August 2023–2024 from -0.245 to 0.207 cm/year. Negative numbers indicate land subsidence, while positive values indicate uplift. There is an increase in land movement, with an average of -0.158 cm/year for land subsidence and 0.176 cm/year for uplift between August 2022 and August 2023 and -109 cm/year between August 2023 and August 2024. The value of land movement increased, increasing by -0.178 cm/year. The average is -0.156.